2023
DOI: 10.1007/s00603-023-03216-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Impedance and Its Applications to Rock and Mining Engineering

Abstract: The characteristic impedance of a rock is defined as the product of the sonic velocity and the density of the rock. Based on previous studies, this article finds that: (1) For an intact rock, its characteristic impedance is a comprehensive physical property, since it is closely related with strengths, fracture toughness, Young’s modulus, and Poisson’s ratio. (2) For rock masses, their characteristic impedances either increase markedly or slightly with increasing depth. (3) The bursts of intact rocks in laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…It is based on the optimal choice of the type of drilling equipment according to the current condition of massif and determination of the sufficient force for penetration into the rock [6]. Assessing drilling efficiency considering rocks' properties is also an important part of research [7].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…It is based on the optimal choice of the type of drilling equipment according to the current condition of massif and determination of the sufficient force for penetration into the rock [6]. Assessing drilling efficiency considering rocks' properties is also an important part of research [7].…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…In that case, the amplitude of the final wave in the blast hole will be greater than that of the original detonation wave. On the other hand, if the characteristic impedance of the stemming material is smaller than that of the explosive, the amplitude of the final wave in the blast hole will be smaller than that of the original wave [5,22,55]. The characteristic impedance of explosives in digital electronic detonators is calculated as Z e = 1130 × 6800 = 7.648 × 10 6 kg/m 2 s, while the characteristic impedance of the clay material (Z clay ) is calculated as Z clay = 2600 × 3480 = 9.048 × 10 6 kg/m 2 s. It can be observed that the characteristic impedance of the clay is greater than that of the explosive, resulting in an increase in detonation wave pressure within the blast hole.…”
Section: Characteristic Impedance Of Stemming Materialsmentioning
confidence: 99%